Academic integrity in the Indonesian academic society: A contextual interpretation of anticorruption mission - Kukuh Fadli Prasetyo (Komisi Pemberantasan Korupsi, 2026)
This manuscript aims to systematically connect the ideas of anticorruption and academic integrity. Due to corruptive symptoms in research and publications, this discussion also leads to improvements in the Anticorruption course and to the formalization of academic integrity into positive law. This is descriptive socio-legal research that employs statutory and conceptual approaches. This study provides an explanatory analysis of the synchronization between integrity in general and academic integrity. Nine anticorruption values correlate with academic integrity and it can be inferred that codes of conduct for research and publication align with the concept of “integrity” in the national anticorruption mission. Secondly, there are two aspects to consider in improving anticorruption education: adjusting learning materials to ensure the topic is relevant to campus circumstances, and involving lecturers in enrichment activities, such as the use of similarity checkers to detect plagiarism. Thirdly, employing legal instruments in academic integrity enforcement indicates the application of formal social control. This paper also suggests pivotal improvements to the legal instruments governing academic integrity, such as the Commission for the Eradication of Corruption ought to conduct a rating of Indonesian higher education institutions based on defined criteria for academic integrity assessment.